Physico-chemical and Microbiological Composition of Composts from Bucharest Municipal Waste - Neata, Gabriela; Teodorescu, Razvan; Dinca, Liviu; Basaraba, Adrian (Agriculture and agricultural science procedia, 2015)
Average composition of household waste in Bucharest has a large variability. The average amount of waste collected is 0.048 m3/man. year compared with the U.S. 1m3/ man. year, South Africa 0.8 m3 / man. year and Australia 0.4 m3/ man. year. These wastes are sorted, the size which could be sorted and reused according to their composition, remaining part, about 64% of the original composition is subject to biodegradation by composting. The material resulting from the biodegradable composting was analyzed in terms of the physical- chemical and microbiological properties. Physical analyzes aimed material granulometry, humidity and porosity. Chemical analyzes were conducted on fractions and consisted in determining pH, salt content and soluble elements such as Ca, Mg, N, P, K, as well as heavy metals (Cu, Zn, Pb, Cd, Ni, etc.). In order to assess biodegradability of the waste material the breath was determined. The results showed variability in physical characteristics between batches of compost from municipal waste, variability of the chemical characteristics of graded according including especially heavy metals and other hazardous elements. This variation indicates that the coarse fractions have a higher amount of N, P, K and small in high fractions of heavy metals. Determination of breath biodegradable material can be a valuable indicator of degradation phenomenon completion.